Methodology to increase the profitability of a Peruvian agro-export company by improving the sales process using the methodologies of Blockchain and Digital Transformation. (LACCEI, 2024)
The export activity has the purpose of selling products or services to markets outside the country's borders producer, because they have comparative advantages with respect to those manufactured or generated in the countries consumers Among the main advantages of exporting are find obtaining foreign currency, job creation, improvement sales and profitability of exporting companies and the income of fiscal resources for exporting countries. In it Peruvian case, exports increased by 11% in the period January to September 2022, which represented an income of US$ 47,827 million compared to the same period of last year. This growth was due to the increase in prices and volumes marketed, it should be noted that the main destinations of the products were China, the United States, the European Union, Japan, South Korea, Canada among others. One of the main exported products is quinoa in bulk, which is later is processed in the country of destination to offer the product finished generating added value and higher benefits. This product has been increasing its export volume due to because it is considered a functional food since it contributes to reducing the risk of various diseases and promotes an improvement in health, its protein value and the amount of amino acids is higher than that of other cereals, which contribute to the process of generating energy, learning, memorization, neural plasticity, liver function, gastric, immune and cardiovascular system. For this reason, It has been established as the main objective of the present research to promote quinoa sales processes packaged and processed to increase the profitability of a Agro-export SME through Blockchain and Transformation Digital.